Effects of anesthesia on cerebral blood flow, metabolism, and neuroprotection - Slupe, Andrew M (J Cereb Blood Flow Metab, 2018)
Administration of anesthetic agents fundamentally shifts the responsibility for maintenance of homeostasis from the patient and their intrinsic physiological regulatory mechanisms to the anesthesiologist. Continuous delivery of oxygen and nutrients to the brain is necessary to prevent irreversible injury and arises from a complex series of regulatory mechanisms that ensure uninterrupted cerebral blood flow. Our understanding of these regulatory mechanisms and the effects of anesthetics on them has been driven by the tireless work of pioneers in the field. It is of paramount importance that the anesthesiologist shares this understanding. Herein, we will review the physiological determinants of cerebral blood flow and how delivery of anesthesia impacts these processes.